PERSEPSI MAHASISWA TERHADAP PENERIMAAN SISTEM DIGITAL LIBRARY BERBASIS TECHNOLOGY ACCEPTANCE MODEL PADA PERPUSTAKAAN PUSAT UNIVERISTAS UDAYANA BALI - Dewi, Ratna Sari; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2015)
This study aims to determine students' perceptions held reception of digital library systems based on the Technology Acceptance Model Udayana University Central Library. Quantitative research used in this study were obtained by distributing questionnaires and interviews with 60 respondents. Multiple linear regression analysis was used to analyze the data in this study. The results of the analysis conducted to obtain findings that the usability perception variables significantly positive effect on user acceptance at Udayana University Central Library. Further results obtained findings that perceived ease significantly positive effect on user acceptance at Udayana University Central Library. Suggestions can be obtained by the cooperation and provide information to the user's e-library to make it easier to use.
Keywords: Persepsi Kegunaan; Persepsi Kemudahan; Penerimaan Pengguna